A novel dual-temperature ejector-compression heat pump cycle - exergetic and economic analyses. (June 2021) - Liu, Jian; Lin, Zhang
Highlights: Two dual-temperature air-source heat-pump systems are compared. Different eco-friendly refrigerants are evaluated in the systems, and their effects are compared. The DAHP-II outperforms the DAHP-I system significantly in terms of economic and exergy efficiency. The refrigerant type shows slightly effect on system exergy efficiency, while affects the economic obvious. Abstract: High-efficiency air source heat pumps are of great importance for energy saving and environmental protection, especially for the cold area in north China. In this study, the thermo-economic performance of the dual-temperature ejector-compression air-source heat-pump (DAHP) cycle, is conducted wherein R1234yf, R290, and R134a are used as refrigerants. Two configurations are examined: DAHP-I (without an ejector, conventional system for comparison) and DAHP-II (enhanced by an ejector). The effects of the principal operating parameters on the system performance, including the exergy destruction ( Ex d_tot ), exergy efficiency ( ηex _sys ) and economic, are investigated, and the two systems are compared. The results indicate that the DAHP-II significantly outperforms the DAHP-I in terms of Ex d_tot, ηex _sys and economic index, and the R290 is the most suitable refrigerant applied for the DAHP-II system. Compared with DAHP-I, the Ex d_tot for DAHP-II is reduced by 24.0%–54.8%. For DAHP-II, although the refrigerant type affects Ex d_tot and ηex _sys slightly, while the effect on economic is noticeable. Comparing with R1234yf, the system using the R134a and R290 as the working fluid, the total annual capital cost rate ( C ˙ t o t ) can be reduced by 6.2% and 11.0% respectively. Besides, the DAHP-II outperforms the DAHP-I system significantly with the R134a, R290 and R1234yf as refrigerant in terms of economic. The relative decrease ratio in total annual capital cost rate ( C ˙ t o t ) are 21.6%, 13.5% and 24.0% respectively. This study provides a basis for the application of DAHP system.